Dominasi dan Hegemoni dalam Cerkak Nglari Nakagawa Karya Suparto Brata - Fitria, Ajeng; Khoirunnisa, Alfi (Sutasoma : Jurnal Sastra Jawa, 2024)
Colonization in Indonesia has been going on for centuries. One of the cruelest forms of domination was that of the Japanese in the Dutch East Indies (Indonesia's name at the time). Over time, Japan became a nightmare that haunted society. This domination goes hand in hand with hegemony as a strengthening of power. This is reflected in a literary work, namely the cerkak entitled Nglari Nakagawa by Suparto Brata. From this discussion, it is hoped that Japanese domination and hegemony can be known and that Nglari Nakagawa can be proven as postcolonial literature. To dissect the story, Gramsci's theory of hegemony is used, supported by other theories, such as orientalism, mimicry, subaltern, and others. The analysis results show that the domination and hegemony carried out by the Japanese caused side effects in the form of mimicry, othering, and subaltern performed by the natives by taking the example of the colonizers. Related to the Japanese rule, the hegemony that prevails in society cannot be concluded equally, but it varies among individuals due to differences in colonization experiences. Looking at the content of Nglari Nakagawa's cerkak, it can be classified as a postcolonial work, one of which is shown by Nakagawa's anomalous existence trying to defy the dominant stereotypes in society.